Penerapan Pendidikan Berbasis Tauhid dalam Pembentukan Karakter Spiritual Anak di TK YAA Bunayya Kota Pekalongan - Isna Yusrina (Perkumpulan Kualitama Edukatika Indonesia, 2021)
In the era of digital technology that is growing rapidly, it is feared that it will have a negative impact on the development of the spiritual character of early childhood. Therefore we need an educational concept that can fortify children from these threats. One of the concepts that can be applied is monotheism-based education, this education is based on the teachings of the Islamic religion which unites Allah. The purpose of this study is to describe the implementation of the concept of monotheism-based education in Yaa Bunayya Kindergarten, Pekalongan City and its implications in the formation of children's spiritual character. This type of research is a case study research that uses a descriptive qualitative approach. The source of the data taken is in the form of purposive sampling with the research subjects consisting of the head of the kindergarten, employees, teachers and group A children aged 4-5 years in Yaa Bunayya Kindergarten, Pekalongan City. Collecting data by observation, interviews and documentation. Meanwhile, for data analysis using data reduction techniques by sorting the data, the findings are then analyzed and presented, then conclusions are drawn at the final stage. From the results of the study, it can be seen that the application of monotheism-based education plays an important role in the formation of the spiritual character of early childhood through exemplary, inculcating concepts and integrative learning which is carried out in Yaa Bunayya Kindergarten, Pekalongan City.